Early Routine Use of Upper GI Contrast Series Post Paraesophageal Hernia Repair: A Single Institution Consecutive Case Series. Issue 3 (June 2019) - Robertson-More, Connal; Prasad, Shalvin; Gill, Richdeep; Church, Neal; Mitchell, Philip; Debru, Estifanos
Abstract : Introduction: There is conflicting evidence with regard to the routine use of upper gastrointestinal contrast series in detecting early complications post paraesophageal hernia repair (PEHR). Methods: All cases booked for a PEHR between January 2007 and September 2015 were identified using hospital records. Standard demographic, operation, and imaging data were extracted. Results: We retrospectively identified 391 PEHR cases between January 2007 and September 2015. The mean age at the index operation was 66.7 years with a female predominance. The majority of index operations were elective and completed for a large paraesophageal hernia. Contrast studies were reported as normal in 70.6%, a leak in 0.3%, an obstruction in 27.9%, and early recurrence in 1.0%. Reoperation was required in 1.8% of cases. Conclusion: Routine upper gastrointestinal contrast studies post-PEHR changed management in 0.8% of cases and were unhelpful in determining the need for early reoperation in 57.1% of cases requiring reoperation.